2018
DOI: 10.1080/09593330.2018.1437779
|View full text |Cite
|
Sign up to set email alerts
|

Alkalinity and external carbon requirements for denitrification-nitrification of coke wastewater

Abstract: The Industrial Emissions Directive requires that coke wastewater is treated to reach an effluent with < 50 mg/L total nitrogen (TN). A shortage of alkalinity (3.6 mg as CaCO/mg [Formula: see text]) in the wastewater limited nitrification to 45%. Various compounds were tested as a source of additional alkalinity, with optimal results being found for sodium carbonate, which enabled 95% nitrification at 300 mg/L (as CaCO). Sodium bicarbonate led to incomplete ammonia oxidation (76%) whilst soda ash prevented nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…When the alkalinity of the influent was 500 mg/L, the treatment efficiency in TOC removal was a little better than for other values of alkalinity. It was reported that when the alkalinity is low, the pH of the system would decrease significantly as the reaction proceeds, which will affect microbial activity and reduce the treatment efficiency of the system [44]. However, in this study, even if the applied alkalinity was as low as 300 mg/L, no obvious decrease of the removal performance was observed.…”
Section: Influence Of Different Influent Alkalinity Values On Toc Removal Efficiencycontrasting
confidence: 58%
See 1 more Smart Citation
“…When the alkalinity of the influent was 500 mg/L, the treatment efficiency in TOC removal was a little better than for other values of alkalinity. It was reported that when the alkalinity is low, the pH of the system would decrease significantly as the reaction proceeds, which will affect microbial activity and reduce the treatment efficiency of the system [44]. However, in this study, even if the applied alkalinity was as low as 300 mg/L, no obvious decrease of the removal performance was observed.…”
Section: Influence Of Different Influent Alkalinity Values On Toc Removal Efficiencycontrasting
confidence: 58%
“…The availability of inorganic carbon was critical for stable nitrification to provide sufficient alkalinity to buffer the acidification resulting from the production of hydrogen ions during ammonia oxidation. Furthermore, the loss of nitrification resulted in a decrease in nitrate concentrations being recycled back to the anoxic reactor, which led to reduced inorganic carbon formation through denitrification, further exacerbating the shortage of inorganic carbon in the aerobic cell [44]. The provision of adequate alkalinity for nitrogen removal was therefore essential for a stable treatment.…”
Section: Influence Of Different Influent Alkalinity Values On Nitrogen Removal Efficiencymentioning
confidence: 99%
“…The addition of sodium carbonate was previously established in coke wastewater samples taken from the full-scale steelworks, as critical for successful nitrification of coke making wastewater through the provision of inorganic carbon for nitrifying bacteria and pH buffering (Raper et al, 2018b). The influent wastewater was therefore dosed with the optimised concentration of sodium carbonate of 523 mg/L as CaCO 3 .…”
Section: Anoxic-aerobic Pilot-plant Configurationmentioning
confidence: 99%
“…The impact of alkalinity addition, micronutrient addition and bioaugmentation was investigated by spiking the coke wastewater. Alkalinity was added at the previously optimized dose of 300 mg L –1 (as CaCO 3 ) through the addition of sodium carbonate (Na 2 CO 3 ) . A micronutrient solution was designed taking account of the coke wastewater characterization and activated sludge nutrient requirements reported by Burgess et al .…”
Section: Methodsmentioning
confidence: 99%
“…Alkalinity was added at the previously optimized dose of 300 mg L -1 (as CaCO 3 ) through the addition of sodium carbonate (Na 2 CO 3 ). 25 A micronutrient solution was designed taking account of the coke wastewater characterization and activated sludge nutrient requirements reported by Burgess et al 6 (Table 1). A commercially available bioaugmentation product was added at doses of 0.1, 0.5 and 1.5 g L -1 .…”
Section: Batch Tests To Assess Effectiveness Of Bioaugmentation Towarmentioning
confidence: 99%